Root mean square radii of the Λ-particle orbits in hypernuclei using potentials of orthogonal shape in arelativistic treatment - Koutroulos, C. G.; Papadopoulos, G. J. (HNPS Advances in Nuclear Physics, 2019)
The root mean square radii of the Λ-particle orbits in hypernuclei are calculated in the ground and first excited states using the Dirac equation with scalar and vector potentials of orthogonal shape. An exact analytic and also approximate expressions are derived for the root mean square ra-' dius of the Λ orbit in its ground state. It is shown that <r > 2 1/2 1/3 ' varies linearly with A ' for the higer mass hypers 1/2 ^ nuclei, Our results in the ground state are compared with the results of Rayet and also with those of Daskaloyannis et. al.